SOCIAL JUSTICE IN JOHN GRISHAM'S THE STREET LAWYER:A SOCIOLOGICAL APPROACH - AZIZAH, FARIDA NUR (2007)
This research paper elaborates the portraits of social justice in John Grisham's novel, The Street Lawyer, which are analyzed through sociological approach. The objectives of the research are to analyze the structural elements of the novel and to analyze the novel based on sociological perspective by identifying the relationship between the novel and the social background of American society at the end of 20th century. This research belongs to qualitative research; the data of the research is the text of a novel entitled The Street Lawyer. Whereas the data source comes from both primary data source which is in the form of the text of the novel being researched and secondary data source such as websites and other sources about the novel and the social background of American Society that support the analysis. The method to analyze the data is descriptive analysis. Having analyzed the novel, the researcher concludes as follows: the social justice in The Street Lawyer is mostly found in the characters drawn by John Grisham who live in the condition of America at that time that was strongly shown by the differences of rich and poor people in America. Poor people included homeless as the under class always get unjust treatment from the authorities' society. While, rich people or the high class that have power or authority do not give opportunity to homeless to get their standard of living. For that reason, the major character as the street lawyer helps them to get the social justice to have the homeless right.